Design and Analysis of Plastic Injection Mould for Holder Casing - Wong, Choon Tat (2004)
The plastic industry involving manufacturing and injection moulding has high growth potential, this is because most of the products today are made from plastic material. The aim of this project is to design a plastic injection mould for producing a holder casing for card or highway toll ticket. This work is concerned with the design, analysis and simulation of the plastic injection mould. The plastic part was designed into two different types of product, but for the same usage function. One part is using clip function and another part is using stick function. In the design section, computer software Pro-Engineer (Pro/E) is used to produce the detail design in 3-dimension (3D) view, the two products are designed into two changeable insert to produce two different types of plastic product and assembly into one mould base.Pro/Manufacturing software is used to develop the programming to run the CNC (Computer Numerical Control) machine. By using ICAM (Intelligent Computer Aided Manufacturing) software to convert the programming from computer code. Moldflow Plastics Insight (MPI) was used to analyse the mould for the design. This software shows how the molten plastic entering the mould during injection process and also the possible defects that might occur. This step normally will eliminate the rework cost and time as all the possible errors are being eliminated before it actually occurs in actual production process. The rework cost is a major problem to the mould making industries. In fabrication process, Computer Numerical Control (CNC), milling, drilling, grinding and Electrode Discharge Machining (EDM) machines were used to machine the mould components. Quality of the mould and injected product depend on the selection of the machines used as well as the processing conditions such as melt temperature, mould temperature and injection pressure. As a conclusion the objective of the project to create a plastic product, analysis by using MPI and create a three plates mould by using slide core insert has been achieved.